KOSENTRASI LIMBAH PERTANIAN SEBAGAI PAKAN ALTERNATIF TERHADAP MORTALITAS DAN PERTUMBUHAN IKAN NILA (OREOCHROMIS NILOTICUS) - Failu, Ismail; Edy, Safrin (Media Agribisnis, 2020)
The research aims (1). Knowing changes concentration in agricultural waste, especially water spinach kale and spinach as a source of food for growth and survival of tilapia (Oreochromis niloticus). (2). Knowing at what concentration of agricultural waste, especially bran kale and spinach as a source of food for growth and survival of tilapia (Oreochromis niloticus). The study was conducted in March to May 2020 in the Village of Liabuku, Bungi sub-district, Baubau town. The experimental design used in this study was a Completely Randomized Design (CRD) with 4 levels of treatment and 3 replications, thus there were 12 experimental units (Gasperstz, 1991), namely: (1) Pellet Feed (Mill) / Control (2) Treatment A (70 kale waste + 20% snail flour + 10 rice bran), (3) Treatment B (60 Kale waste + 30% snail flour + 10 rice bran) ), (4) Treatment C (50% kale waste + 40% snail flour + 10 rice bran). The provision of concentrations in the form of agricultural waste, especially kale, snail flour, and bran as a source of food does not have a significant effect on absolute growth, survival rates, and feed conversion to tilapia (Oreochromis niloticus) that are kept in ponds using nets. Absolute growth, survival rates, and the best feed conversion at treatment C (50% Kale Waste + 40% snail flour + rice bran 10) which are maintained in a pond using a net. Keywords: Concentration of Agricultural Waste, Mortality and Growth